2018
DOI: 10.1002/adhm.201800427
|View full text |Cite
|
Sign up to set email alerts
|

Multicombination Approach Suppresses Listeria monocytogenes‐Induced Septicemia‐Associated Acute Hepatic Failure: The Role of iRhom2 Signaling

Abstract: The mortality rate of acute liver failure significantly increases due to fatal septicemia. Inactive rhomboid protein 2 (iRhom2) is an essential regulator of shedding TNF-α by trafficking with TNF-α converting enzyme (TACE). Fisetin, a flavonoid present in various fruits and plants, possesses anti-oxidative stress and anti-inflammatory activities. Here, multi-combination nanoparticles Fe@Au conjugated with fisetin, iRhom2 small interfering RNA (siRNA), and TNF-α inhibitor (FN) are prepared to examine their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Inactive rhomboid protein 2 (iRhom2), also known as Rhbdf2, is an inactive member of the rhomboid intramembrane proteinase family of serine proteases that has been shown to be involved in the regulation and trafficking of inflammatory responses. (12)(13)(14)(15) With the alteration of the innate immunity status, iRhom2 activity in macrophages is markedly up-regulated, and iRhom2 enhances maturation and secretion of TNFα through trafficking with a disintegrin and metalloprotease 17 (ADAM17), activating downstream signaling cascades involving TNFα, phosphorylated NF-κB, and various cytokines or chemokines, thereby strengthening the inflammatory reaction and promoting macrophage infiltration. (15) These recent studies have reported various ways in which iRhom2 regulates stimulus-mediated immune responses in viral infection, inflammatory injury, and hepatic failure.…”
Section: Irhom2 Promotes Hepatic Steatosis By Activating Map3k7-depen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inactive rhomboid protein 2 (iRhom2), also known as Rhbdf2, is an inactive member of the rhomboid intramembrane proteinase family of serine proteases that has been shown to be involved in the regulation and trafficking of inflammatory responses. (12)(13)(14)(15) With the alteration of the innate immunity status, iRhom2 activity in macrophages is markedly up-regulated, and iRhom2 enhances maturation and secretion of TNFα through trafficking with a disintegrin and metalloprotease 17 (ADAM17), activating downstream signaling cascades involving TNFα, phosphorylated NF-κB, and various cytokines or chemokines, thereby strengthening the inflammatory reaction and promoting macrophage infiltration. (15) These recent studies have reported various ways in which iRhom2 regulates stimulus-mediated immune responses in viral infection, inflammatory injury, and hepatic failure.…”
Section: Irhom2 Promotes Hepatic Steatosis By Activating Map3k7-depen...mentioning
confidence: 99%
“…( 16 ) Furthermore, iRhom2 overactivation facilitates inflammatory responses in acute hepatic injury and systemic metabolism syndrome. ( 15 ) However, to the best of our knowledge, a role of iRhom2 in systemic insulin resistance, inflammation, or hepatic steatosis has not been reported. In light of these findings, there is an urgent need to explain the exact role of iRhom2 in the development and progression of hepatic inflammation, steatosis, and insulin resistance.…”
mentioning
confidence: 92%
“…As we previously reported, iRhom2 was involved in hepatic injury induced by PM 2.5 through modulating inflammatory response, and loss of iRhom2 significantly attenuated PM 2.5 -triggered inflammation in liver tissue samples, along with remarkable reduction of TACE/TNFRs [17] . Recently, we reported that reducing iRhom2 could alleviate acute hepatic injury by blocking inflammatory response [24] . Therefore, we hypothesized that iRhom2 might be also involved in the regulation of renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Fisetin, a natural antioxidant, is found in various vegetables and fruits [ 138 , 139 ]. TNF-α inhibitor manifested excellent anti-inflammatory and antioxidant effects in Listeria monocytogenes induced fatal septicemia-associated ALF [ 140 ]. The nanocomposite inhibited macrophage activation-related inactive rhomboid protein 2/TNF-α converting enzyme/TNF-α signaling and restored nuclear factor erythroid-2-related factor 2 to relieve Listeria monocytogenes-induced metabolic disorder and septicemia-associated systemic inflammation.…”
Section: Nanomedicine For Therapy Of Acute Liver Failurementioning
confidence: 99%